Membangun Narasi Politik melalui Humor dan Troll: Studi Kasus Akun Instagram Kementerian Kegelapan - Muhammad Setiawan; Wasyihatul Akmal; Zachraini Nuur (Talenta Publisher, 2026)
This study discusses how the Instagram account @kementeriankegelapan builds political narratives through humor and trolling as a form of alternative political participation in Indonesia's digital space. In the context of the rise of internet-based political culture, humor and trolling are understood not merely as entertainment, but as symbolic communication strategies that reflect both resistance and domination of mainstream political discourse. This study uses a qualitative approach with a case study method and is based on the theory of trolling by Whitney Phillips and Ryan M. Milner. The results show that the practice of humor and trolling on this account is ambivalent: it functions as a mechanism for criticizing authority, but also as a new style of communication that strengthens the account's position in framing public opinion. Through irony, parody, and bureaucratic absurdity, these accounts disrupt the legitimacy of political symbols while creating an inclusive space for political expression for the younger generation. In addition, active audience participation shows that digital humor plays an important role in forming collaborative political communities on social media. This study concludes that humor and trolling are effective instruments in articulating alternative political narratives in the social media era, marking a shift in the form of political participation from the formal realm to creative and reflective cultural expression.